INDUSTRI KONSTRUKSI DI ERA INDUSTRI 4.0 - Akbar Alfa (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2018)
The industrial revolution was introduced first in the mid-19th century. It was noted that the beginning of the industrial revolution occurred approximately between 1760-1830. This revolution then continued to grow and experience a peak in the mid-19th century. Over time, Industry 4.0 has introduced flexible mass production technology. The machine will operate independently or coordinate with humans. Industry 4.0 is an approach to control the production process by synchronizing time by integrating and adjusting production. Industry 4.0 is used in three interrelated factors; 1) digitalization and interaction of the economy with simple techniques towards economic networking with complex techniques; 2) digitizing products and services; and 3) new market models. Construction is an arrangement (model, layout) of a building (bridge, house, etc.) Although construction activities are known as one job, in reality construction is a unit of activity consisting of several different jobs. This study uses literature study methods. Several concepts taken from various related literature are analyzed in harmony with the topics discussed. The positive influence of industry 4.0 in the form of resource effectiveness and efficiency and production costs despite having an impact on reducing employment. Industry 4.0 requires workers who have skills in digital literacy, technology literacy, and human literacy.